2010
DOI: 10.3758/s13415-010-0010-1
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of emotion areas through neurofeedback with a focus on positive mood

Abstract: Real-time functional magnetic resonance imaging can be used to feed back signal changes from the brain to participants such that they can train to modulate activation levels in specific brain areas. Here we present the first study combining up-regulation of brain areas for positive emotions with psychometric measures to assess the effect of successful self-regulation on subsequent mood. We localized brain areas associated with positive emotions through presentation of standardized pictures with positive valenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 26 publications
6
75
1
Order By: Relevance
“…For example, healthy individuals showed the ability to self-regulate brain activity in neuroanatomical structures often associated with affect (e.g., insula, amygdala, prefrontal cortex (PFC), and anterior cingulated cortex (ACC)) (Hamilton, Glover, Hsu, Johnson, & Gotlib, 2011;Johnston et al, 2011;Posse et al, 2003;Sitaram, Caria, et al, 2007;Zotev et al, 2011 Subramanian et al, 2011) and depression (e.g., Linden et al, 2012;Young et al, 2014). Although these clinical studies represent mostly nascent efforts in line with pilot data and usually draw on small samples and largely unreplicated assays, the emerging tenor from these preliminary findings seems to speak favorably to the clinical potential of rtfMRI-nf.…”
Section: Fmrimentioning
confidence: 99%
“…For example, healthy individuals showed the ability to self-regulate brain activity in neuroanatomical structures often associated with affect (e.g., insula, amygdala, prefrontal cortex (PFC), and anterior cingulated cortex (ACC)) (Hamilton, Glover, Hsu, Johnson, & Gotlib, 2011;Johnston et al, 2011;Posse et al, 2003;Sitaram, Caria, et al, 2007;Zotev et al, 2011 Subramanian et al, 2011) and depression (e.g., Linden et al, 2012;Young et al, 2014). Although these clinical studies represent mostly nascent efforts in line with pilot data and usually draw on small samples and largely unreplicated assays, the emerging tenor from these preliminary findings seems to speak favorably to the clinical potential of rtfMRI-nf.…”
Section: Fmrimentioning
confidence: 99%
“…In order to achieve such upregulation, the strategy of positive autobiographical memory (AM) retrieval was selected based on findings of amygdala activity (with other medial temporal regions) during AM retrieval (Greenberg et al, 2005), and because it is commonly reported by participants post-hoc as an effective strategy in neurofeedback studies targeting emotional processing brain regions (Caria et al, 2007;Johnston et al, 2011;Linden et al, 2012). More importantly, depressed individuals are impaired at recalling specific and positive AMs (van Vreeswijk and De Wilde, 2004;Young et al, 2012Young et al, , 2013; therefore, reinforcement in the associated brain circuit is hypothesized to occur with the neurofeedback training, which may also help normalize this deficit.…”
mentioning
confidence: 99%
“…Thus, it has the potential to be useful in upregulating or downregulating neural activity in disease states. Self-regulation of emotion networks through fMRI-based neurofeedback (Caria et al, 2010;Johnston et al, 2011) has been used in schizophrenia (Ruiz et al, 2011), and fMRI has also been used to document effects of neurofeedback with electroencephalography (EEG) in attention deficit/hyperactivity disorder (Beauregard and LĂ©vesque, 2006).…”
Section: Introductionmentioning
confidence: 99%